2020
DOI: 10.1177/2164956120905817
|View full text |Cite
|
Sign up to set email alerts
|

Integrative East–West Medicine Intervention for Chronic Daily Headache: A Case Report and Care Perspective

Abstract: Chronic daily headache is a group of headache syndromes including most commonly chronic migraine and chronic tension-type headache, which often overlap, are complicated by medication overuse and are disabling, costly, and variable responsive to western pharmacotherapeutic interventions. There is growing research and awareness of integrative health approaches and therapies to address patients with chronic headache, yet limited examples of how to deliver this approach. This article reviews a commonly seen challe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…As a result, his headache symptoms improved markedly and generally disappeared. Routine chronic headache is a group of headache syndromes, mainly chronic migraine and CTTH [ 1 , 5 ]. CTTH, the chronic form of TTH, is said to affect 0.5–4.8% of the population worldwide [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, his headache symptoms improved markedly and generally disappeared. Routine chronic headache is a group of headache syndromes, mainly chronic migraine and CTTH [ 1 , 5 ]. CTTH, the chronic form of TTH, is said to affect 0.5–4.8% of the population worldwide [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Chronic tension-type headache (CTTH), along with chronic migraine, is included in a group of headache syndromes as chronic daily headache (CDH) [ 1 ]. Treatment includes oral medications, trigger point injections, and botulinum toxin (BoNT) therapy, but treatment can be difficult [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have indicated that TCM therapies, such as herbal medicine and acupuncture, can potentially decrease proteinuria, enhance kidney function, and alleviate symptoms in persons diagnosed with CKD [38]. Nonetheless, the wide range of therapeutic approaches within TCM and the imperative for thorough scientific investigation underscores the significance of seeking guidance from trained practitioners [39].…”
Section: Effectiveness Of Complementary Therapies In Renal Carementioning
confidence: 99%
“…In summary, successfully integrating complementary medicines into conventional healthcare necessitates a collaborative endeavor encompassing research, education, legislative modifications, and enhanced interprofessional communication within the healthcare community [39]. By adopting a patient-centered approach and adhering to evidence-based practice, healthcare providers can effectively address these obstacles and deliver comprehensive, holistic treatment that caters to patients' varied requirements and preferences [40].…”
Section: Prospects For Future Research and Approaches To Addressing O...mentioning
confidence: 99%